Knowledge driven development : private extension and global lessons - Zhou, Yuan; Sures, Babu (Public food policy and global development., 2015)
Knowledge Driven Development: Private Extension and Global Lessons uses actual cases written specifically to study the role and capacity of private companies in knowledge sharing and intensification through agricultural extension. Descriptions of specific models and approaches are teased out of complex situations exhibiting a range of agricultural, regulatory, socio-economic variables. Illustrative cases focus on a particular agricultural value chain and elaborate the special feature of the associated private extension system. Chapters presenting individual cases of private extension also.